Does Use of an Electronic Health Record with Dental Diagnostic System Terminology Promote Dental Students' Critical Thinking?. Issue 6 (1st June 2015) - Reed, Susan G.; Adibi, Shawn S.; Coover, Mullen; Gellin, Robert G.; Wahlquist, Amy E.; AbdulRahiman, Anitha; Hamil, Lindsey H.; Walji, Muhammad F.; O'Neill, Paula; Kalenderian, Elsbeth
Abstract : The Consortium for Oral Health Research and Informatics (COHRI) is leading the way in use of the Dental Diagnostic System (DDS) terminology in the axiUm electronic health record (EHR). This collaborative pilot study had two aims: 1) to investigate whether use of the DDS terms positively impacted predoctoral dental students' critical thinking skills measured by the Health Sciences Reasoning Test (HSRT), and 2) to refine study protocols. The study design was a natural experiment with cross‐sectional data collection using the HSRT for 15 classes (2013–17) of students at three dental schools. Characteristics of students who had been exposed to the DDS terms were compared with students who had not, and the differences were tested by t‐tests or chi‐square tests. Generalized linear models were used to evaluate the relationship between exposure and outcome on the overall critical thinking score. The results showed that exposure was significantly related to overall score (p=0.01), with not‐exposed students having lower mean overall scores. This study thus demonstrated a positive impact of using the DDS terminology in an EHR on the critical thinking skills of predoctoral dental students in three COHRI schools as measured by their overall score on the HSRT. These preliminary findings support future research to further evaluate a proposed model of critical thinking in clinical dentistry.